IMPACT OF SERVICE QUALITY AND THE PROMOTION OF THE PUBLIC S DECISION TO SAVE THE BANK NAGARI BRANCH SOLOK SELATAN - Susanti, Fitria; Sari, Mareta Kemala; Sumarni, Sumarni (Pendidikan Ekonomi, 2014)
ABSTRACT Issues that are examined in this study is the impact of service quality and the promotion of the public s decision to save the Bank Nagari Branch Solok Selatan . The purpose of this study was to analyze the influence of the effect of service quality and the promotion of the public s decision to save the Bank Nagari Branch Solok Selatan . The methodology used in this study is the method of multiple linear regression analysis . The technique of collecting data using questionnaires , such as statements regarding the quality of service and promotion of the community s decision to save the Bank Nagari Branch Solok Selatan . Collected through documentation related to the bank . First results showed that : The quality of care affect the society s decision to save the Bank Nagari Branch Solok Selatan indicated by the coefficient value of 0.403 with significant value of 0.000 < α = 0.05 . Second : Promotion effect on people s decision to save the Bank Nagari Branch Solok Selatan indicated by a coefficient of 0.367 with significant value of 0.000 < α = 0.05 . Third : Service quality and Promotions jointly influence the public s decision to save the Bank Nagari Branch Solok Selatan indicated by the F - statistic of 50.148 , with a significant value of 0.000 < α = 5 % , and the R - squared value of 0.511 amounted to 51.1 % , which means the decision to save the people affected by the variable quality of service and promotion while the rest is explained by other variables . From this study the authors concluded that the quality of service and promotion effect on people s decision to save the Bank Nagari Branch Solok Solok Selatan , for it suggested to the management of the bank to pay more attention to the quality of service provided to clients and work to improve the promotion in order to increase the public s decision to save in Bank Nagari Branch Solok Selatan ,